Optimizing surgical outcomes through increased familial support in the perioperative period - Assaf, Nour; Bazzi, Hussein; Ghanem, Kristina; Saasouh, Wael (Frontiers in Anesthesiology, 2025)
Familial support in perioperative care is increasingly being recognized as essential for better surgical outcomes, treatment protocols, and overall recovery. Recent work suggests that standardized family involvement leads to measurable improvements, including reduced postoperative delirium (POD) and complications, lower anxiety, shorter hospital stay, and increased patient and family satisfaction. Examples include the Tailored, Family-Involved Hospital Elder Life Program (t-HELP), which reduced POD incidence from 19.4%–2.6% while preserving functional and cognitive changes in elderly; as well as the Family Involvement Program (FIP), which integrates caregiver training, ward-round participation, and post-discharge support to reduce pneumonia, delirium, and readmissions incidences. Despite these benefits, family engagement remains inconsistently integrated into perioperative settings due to the lack of policies, limited staff training, cultural differences, and workflow concerns. This study reviews recent high-quality evidence, identifies common obstacles, and proposes a structured operational framework for family support comprising: 1. structured perioperative updates at defined milestones; 2. need-based caregiver training; 3. active family inclusion in care planning; 4. integration of digital home monitoring systems; and 5. cultural tailoring of policies and educational materials. If adopted by healthcare systems, this framework can help build perioperative protocols with dedicated resources, supportive policies and leadership endorsement. Future research should explore multicenter implementation, cost-effectiveness, and long-term outcomes of culturally-adapted, digitally-enabled family engagement models.